KETAHANAN PANGAN DAN PEMBANGUNAN MANUSIA SERTA DAMPAKNYA TERHADAP KEGIATAN EKONOMI : STUDI KASUS NEGARA ASEAN - jakaria jakaria; Justine Tanuwijaya; M. Yudhi Luthfi (Media Ekonomi, 2021)
Examine  the effect of food security which consists of the dimensions of affordability, availability, quality & safety and natural resources on the human development index (HDI) and its impact on the level of economic activity for countries in the Southeast Asia region. The research design uses hypothesis testing of the effect of the independent variable on the dependent variable using the Structural Equation Model (SEM). This study uses sample of 9 countries in Southeast Asia region (Cambodia, Indonesia, Laos, Malaysia, Myanmar, Philippines, Singapore, Thailand and Vietnam) with a study period of 9 years (20120-2020). The research findings show that the dimensions of affordability and quality & safety have a significant positive effect on HDI, while the dimensions of availability and natural resources have no positive effect on HDI. Other findings also prove that HDI has a positive effect on the level of economic activity (GDP).